Versatile Travels & Tours Ltd. and its entry in world of online booking engine as flyversatile.com - Hossain, Tahsin Arbid (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.